Co-inoculation of peanut (Arachis hypogaea L.) with Bradyrhizobium and Azospirillum promotes greater tolerance to drought (Research, Society and Development, 2020)
The use of growth-promoting rhizobacteria can be a management strategy to mitigate the effects of water deficiency on plant growth and development by modifying physiological metabolism and promoting greater drought tolerance. This study aimed to investigate the effects of seed inoculation with Bradyrhizobium japonicum and Azospirillum brasilense alone and combined on the growth and induction of tolerance of peanut plants (Arachis hypogaea L., cv. RUNNER IAC 886) to water restriction. The experimental design adopted was that of random blocks in a 3 × 4 factorial scheme, consisting of three levels of irrigation [100% of the soil's water retention capacity (control), 50% of the control (moderate stress) and 25% of the control (severe stress)] and by four inoculation treatments [control (without inoculation), inoculation with B. japonicum, inoculation with A. brasilense and seed co-inoculation with B. japonicum and A. brasilense, with four replications. Water restriction was imposed at the beginning of the appearance of the gynophore, 40 days after the emergence of the plants, for a period of 18 days. Plants exposed to conditions of severe water restriction reduced plant height (32%), leaf area (44%), root volume (47%), shoot dry matter (35%) and root dry matter (37%) when compared to plants under control conditions. After 18 days of exposure of the plants to water restriction, the relative water content, membrane integrity, plant height, leaf area, root volume and dry matter of shoots and roots were measured. Inoculation with B. japonicum and A. brasilense alone or in combination improved the cell membrane integrity by 7% and reduced the water losses of peanut leaves exposed to water deficiency by 8%. Inoculation with A. brasilense alone or in combination with B. japonicum resulted in higher plant height (21%) and higher root dry matter (23%) when compared to plants not inoculated under severe water restriction conditions. Our results suggest that inoculation with B. japonicum and A. brasilense in isolation or in combination can mitigate the adverse effects of water deficiency, maintaining the growth and dry matter accumulation of peanut plants when exposed to water restriction. Therefore, the use of these rhizobacteria in the peanut cropping can be an alternative of management in conditions subject to the occurrence of water deficiency to confer greater tolerance of the plants to drought.